AB1235-HPR Chronic Neck Pain Influences Jaw Muscles Recruitment During a Biting Task. (9th June 2015) - Testa, M.; Geri, T.; Gizzi, L.; Petzke, F.; Falla, D.
Abstract : Background: Mastication requires a high degree of coordination between jaw and neck muscles. The spino-trigeminal system supports the hypothesis that the presence of pain in one of these two regions could affect the motor behaviour of the other. While experimental evidences showed that patients with temporomandibular disorders display electromyographic alterations of the neck flexor and extensor muscle (Armijo-Olivo and Magee, 2013), alterations of the jaw muscles in patients with neck pain have not been investigated yet. Objectives: To investigate precision, accuracy and electromyographic activity of jaw muscles contraction during a unilateral bite task in subjects with neck pain. Methods: Ten subjects with chronic neck pain and an age and gender-matched sample of healthy individuals volunteered for this study. The maximal voluntary bite force (MVC) was measured with a flexible force transducer positioned between the first molar teeth and used to set up a biting task requiring the subjects to match 4 targets (10, 30, 50 and 70%MVC) displayed on a computer monitor. Electromyographic (EMG) signals of the masseter and anterior temporalis muscles were recorded bilaterally. The subject's force performance was measured using error indices from the reference target like the Mean Distance (MD), Offset Error (OE) and the Standard Deviation (SD) of the delivered force. The Root Mean Square (RMS) of the electromyogram was calculated to detect differences in muscular activity. Between-group differences of the force indices (MD, OE, SD) and EMG activity (RMS) were assessed through Kruskal-Wallis test significance level was set to 0.05. Results: There were no significant between-group differences in force production for MD (H =0.38, P=0.5), OE (H =1.81, P=0.2) and SD (H =0.26, P=0.6). A significant difference in electromyographic activity was however detected for the masseter muscle (H =7.19, P=0.007, please refer to Figure) but not for temporalis (H =3.82, P=0.05). Conclusions: This study demonstrates that patients with neck pain present higher masticatory muscle activity during a unilateral biting task. Our results support the strong functional relationship between temporomandibular and neck regions and invite to consider, also in clinical setting, the possibility that a disorder affecting one region can have consequences on the functionality of the other. In fact, even though the motor output was comparable between groups, subjects with neck pain displayed higher RMS activity of masseter muscle to deliver the same force. References: Armijo-Olivo S, Magee D. Cervical musculoskeletal impairments and temporomandibular disorders. J Oral Maxillofac Res. 2013;3:e4. Disclosure of Interest: None declared